First detection of Eimeria species in Myanmar domestic goats with both microscopic and molecular methods - Bawm Saw; Win Tay Zar Bhone; Win Shwe Yee; Htun Lat Lat; Nakao Ryo; Katakura Ken (Parasite, 2020)
Coccidiosis is of great economic importance in many farm animals. This study involved analysis of 280 faecal samples collected from 12 traditional goat farms from Nay Pyi Taw area, Myanmar. Faecal samples were examined by the flotation method and concentrated oocysts were identified on the basis of morphological characters. Of 280 faecal samples examined, 168 (60.0%) were positive for Eimeria oocysts. Three different Eimeria species were identified and their positive detection rates in the herd were: E. arloingi (25.4%), followed by E. hirci (20.7%) and E. christenseni (13.9%). Identifications were confirmed by 18S rDNA and COI sequences. 18S rDNA sequences showed 100% homology with, respectively, E. christenseni reported from Australia, E. arloingi reported from Australia and Iran, and E. hirci from Australia. COI sequences of E. christenseni, E. hirci, and E. arloingi, respectively, exhibited 98.9%, 98.4%, and 98.5% similarities with those reported from Australia. This is the first report of Eimeria infection in Myanmar goats.